Factors Influencing Collaboration Between Academic Researchers And Industry Practitioners For Commercialising Research Product - Md Zaini, Syamimi (2017)
In a competitive globalised world, research product commercialisation has been recognised as a new engine for wealth creation of a nation. Malaysia is not lagging behind in the mission of creating wealth and prosperities for the country. However, studies reveal that commercialisation of research product in Malaysia is still not at satisfactory level. One of the reasons is due to the weakness of collaboration between academic researchers and industry practitioners in commercialising research products. As such, this research aimed to investigate factors which influence a collaboration between academic researchers and industry practitioners in commercialising research products. For this purpose, a case study was employed within the context of the Malaysian Technical Universities (MTU) in order to gain an in depth understanding. As a case study requires multiple sources of data collection, a document analysis on Intellectual Property (IP) policies of MTU and interviews session with eight academic researchers and four industry practitioners have been conducted. The findings of this study yielded that four elements were needed in order to achieve collaboration between academic researchers and industry practitioners in commercialising research products; university, academic researcher, industry practitioner and research products. These elements are interdependent in which each role is crucial in complementing others in order to achieve high level of collaboration. The relationship between the elements were shaped by interdependence theory where they are required to promote each other‘s effort. If one element is missing, it would be difficult to achieve the collaboration. The findings were then developed into a framework. This study contributes to the literature by establishing the framework of the factors influencing collaboration between academic researchers and industry practitioners for research products commercialisation. Besides, this study also portrays a comparison of the perceptions from academic researchers and industry practitioners in discovering the real issues of collaboration and factors influencing them in achieving a collaboration in research products commercialisation endeavour. The findings of this study will be able to give valuable insights for academic researchers as well as industry practitioners to plan their strategies in commercialising research products. A series of recommendation were presented as well.